ANALISIS UNJUK KERJA WIRELESS DISTRIBUTION SYSTEM PADA JARINGAN BERBASIS MIKROTIK - Fauzi, Imam; Jusak, Jusak; Pamungkas, Johan (Journal of Control and Network Systems (JCONES), 2016)
Wireless distribution system (WDS) is a system to expand the wireless network and MAC address as destination addressess. Some documents have discussed WDS technology which one of it says that there is decline in throughput almost half a percent.In this paper, we examine how far the WDS impacts on packet loss and delay that occur when using different topologies in the network based Mikrotik. In the test, we first determined the topology and the location of the router and then we configured WDS route with registering the path between the router's MAC address. Secondly, we delivered streaming videos from server to the client and run the network monitoring software to record the network activity. Thirdly, we analyzed the delay, throughput, and packet loss as a result of the monitoring network.Based on the research examination, it is shown that there is no significant difference between the topology scheme 1 and the topology scheme 2. The performance of the router Master, router 1 and router 2 between topology 1 and topology 2, using the testing parameters: delay, throughput, and packet loss are the same. This is mainly because both of topologies have the same number of hops. On the other hand, there are significant difference in term of delay, throughput and packet loss for router 3 and router 4 both topologies. This is due to that the Master router to router 3 and the router 4 in the topology 2 has more hops than topology 1.